Alterations of white matter integrity associated with cognitive deficits in patients with glioma. Issue 7 (15th May 2020) - Liu, Dongming; Liu, Yong; Hu, Xinhua; Hu, Guanjie; Yang, Kun; Xiao, Chaoyong; Hu, Jun; Li, Zonghong; Zou, Yuanjie; Chen, Jiu; Liu, Hongyi
Abstract: Objective: This study aimed to investigate the characteristic of brain structural connections in glioma patients and further evaluate the relationship between changes in the white matter tracts and cognitive decline. Methods: This retrospective study included a total of 35 subjects with glioma and 14 demographically matched healthy controls, who underwent diffusion tensor imaging scans and formal neuropsychological assessment tests. Fractional anisotropy (FA) values of white matter tracts were derived from atlas‐based analysis to compare group differences. Furthermore, subgroup‐level analysis was performed to differentiate the effects of tumor location on white matter tracts. Partial correlation analysis was used to examine the associations between neurocognitive assessments and the integrity of tracts. Region of interest‐based network analysis was performed to validate the alteration of structural brain network in subjects with glioma. Results: Compared with controls, subjects with glioma exhibited reduced FA values in the right uncinate fasciculus. Besides, subjects with glioma exhibited worse performance in several cognitive assessments. Partial correlation analysis indicated that the FA value in the right superior longitudinal fasciculus temporal part was significantly positively correlated with scores of visual–spatial abilities in subjects with glioma in the right temporal lobe ( r = .932, p = .002). Region of interest‐based network analysis revealed that subjects with glioma exhibited reduced FA, fiber length (FL), and fiber number (FN) between specific brain regions compared with controls. Conclusion: The present study demonstrated the reduced integrity of white matter tracts and altered structural connectivity in brain networks in patients with glioma. Notably, white matter tracts in the right hemisphere might be vulnerable to the effects of a frontal or temporal lesion and might be associated with deficient cognitive function. Abstract : In this work, we explored the effect of the heterogeneous gliomas on multiple WM tracts and global structural network. We attempted to utilize tract‐based DTI analysis to identify the alteration of the white matter (WM) tracts in patients with glioma. The cognitive characteristics of the patients with glioma also studied.